Transgenders in Kerala- Realisation of their Identity. - Krishna, Gayathri (Journal of Social Work Education and Practice, 2023)
The paper tries to unfold the life journey of transgenders in Kerala and their experiences of interaction with societal institutions that have shaped their identity. The state of Kerala does not have a “traditional” transgender culture such as hijras and hence transgenders in the state have had less exposure to a transgender socialisation. A qualitative descriptive enquiry is done to draw out the various stages in the identity realisation of transgender individuals. The backdrop of the socialisation in their life is drawn out to understand transgender identities in depth. The relations of the transgender individuals with societal institutions such as family, school, etc. keep changing over these stages and take both positive and negative connotations.
Keywords: Transgender; Kerala; Realization; Identity; Culture; Socialisation